Investigation of the Protective Effects of Nigella Sativa Oil and Thymoquinone in Radiation Exposed Rats - Demirel, Can; Gözen, Hafiza; Akan, Müslüm; Tarakçıoğlu, Mehmet (European Journal of Therapeutics, 2023)
Objective: It is not always possible to treat early and late side effects due to radiotherapy. In this study, the effects of free radicals on the oxidant antioxidant system were investigated in comparison with the clinical use of WR-2721 in the prevention and treatment of side effects caused by free radicals. Methods: According to the experimental protocol, rats were randomly assigned to five groups: Control Group (K; n=10), Radiotherapy Group (R; n=10), Nigella sativa oil Group (NSO; n=10; 2.4 g/kg/day), Nigella sativa oil+Radiotherapy Group (R+NSO; n=10; 60 min; 2.4 g/kg/day), Radiotherapy+Amifostine Group (R+WR-2721; n=10; 200 mg / kg / day; 60 min before 60 min. Radiotherapy was applied to the rats using radioactive cobalt-60 teletherapy machine in a single dose of 8 Gy to the whole body area as SSD 40 cm. The study was completed in 72 h following radiation application, and the rats were sacrificed by decapitation. Oxidative Stress Index (OSİ) Total Oxidative Stress (TOS) Total Antioxidant Status(TAS) malondialdehyde (MDA), nitric oxide (NO), myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT) parameters were measured. Results: According to these results, WR has more positive effects on MPO and CAT values when NSO on MDA values. There was no statistically significant difference in TOS, OSI, NO, TAS, SOD, CAT values between the R + NSO and K Groups. Compared to the R Group, TOS, OSI, NO, MDA levels significantly decreased and TAS, SOD, GSH, CAT levels significantly increased in the R+NSO Group. Conclusion: In this study, we have shown that Nigella sativa oil is effective in radiation-induced damage on the liver oxidative stress and nitrosative stress. Further studies should be conducted to investigate different tissues, with different radiation intensities and different concentrations of Nigella sativa oil.